The impact of the COVID-19 pandemic on medical assistance in dying in Canada and the relationship of public health laws to private understandings of the legal order. Issue 1 (11th December 2020) - Tremblay-Huet, Sabrina; McMorrow, Thomas; Wiebe, Ellen; Kelly, Michaela; Hennawy, Mirna; Sum, Brian
ABSTRACT: Drawing on interviews we conducted with 15 medical assistance in dying (MAiD) providers from across Canada, we examine how physicians and nurse practitioners reconcile respect for the new, changing rules brought upon by the coronavirus disease 2019 (COVID-19) pandemic, along with their existing legal obligations and ethical commitments as health care professionals and MAiD providers. Our respondents reported situations where they did not follow or did not insist on others following the applicable public health rules. We identify a variety of techniques that they deployed either to minimize, rationalize, justify or excuse deviations from the relevant public health rules. They implicitly invoked the exceptionality and emotionality of the MAiD context, especially in the time of COVID, when offering their accounts and explanations. What respondents relate about their experiences providing MAiD during the COVID pandemic offers occasion to reflect on the role actors themselves play in giving meaning (if not coherence) to the potentially conflicting normative expectations to which they are subject.